Niche Tourism and Sustainability : Perspectives, Practices and Prospects - (:unkn) unknown (My University, 2025)
Niche tourism, also known as special interest tourism, refers to specialized tourism products offered to a small group of tourists. Examples include ecotourism, rural tourism, birdwatching tourism, dark tourism and motorcycle tourism. Regarded as the antidote to mass tourism, niche tourism has become particularly popular in recent years as a tourism developmental option that can address the problems caused by mass tourism including overtourism. It is commonly acknowledged that niche tourism fosters responsible tourism practices, minimizes negative tourism impacts and helps preserve the environment and culture of destinations; thereby, promoting sustainability in tourism. Likewise, niche tourism seems to be better equipped to address the needs and preferences of today's sophisticated and diverse tourist market. Despite these advantages, niche tourism development faces challenges such as overlap with mass tourism due to growing numbers of visitors, promotion of products that are not environmentally friendly and limited economic benefits being directed to the local community. This book is a collection of 12 conceptual and empirical chapters presenting niche tourism cases from around the world. It examines tourist behaviour and experiences, resident perspectives, implementation practices and future prospects, and contributes to the debate on tourism development and sustainability.